Hvor godt er karplantefloraen i Norge kartlagt? 3. Nordland - Alm, Torbjørn; Pedersen, Oddvar (Norsk Botanisk Forening, 2017)
Published version also available in Blyttia : Norsk botanisk forenings tidsskrift.75(3):141-175. Nordland is Norway’s second largest county, with an areal extent of 38,482 km 2 . In general, Nordland is reasonably well covered in terms of botanical exploration, with few blank areas. No flora covering the entire area has ever been compiled, but floristic surveys are available from several part areas, ranging in size from single localities to large districts. Still, the absence of a comprehensive account of the flora hampers comparison with Troms and Finnmark, e.g. in terms of establishing the number of new species recorded during recent years. About 42 new, indigenous taxa and at least 216 introduced taxa have been added to the flora (or identified) since 1940. Maps showing the distribution of herbarium specimens collected in Nordland reveal a number of sparsely studied areas that should receive attention during future field wor